Menakar Implementasi Kebebasan Pers di Indonesia pada Era Kepemimpinan Joko Widodo - Faesal Mubarok (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2021)
Press freedom is an important part of a democratic state formation system. In line with the fourth pillar in building a democratic state and society, press freedom is an absolute must. This study aims to measure the extent to which the implementation of press freedom materialized during Joko Widodo's leadership. Researchers used a qualitative approach with descriptive methods and processed data based on literature study. The analysis shows that during the Joko Widodo administration period, the ban on press freedom in Indonesia could still be felt. Looking at the facts that the oligopoly practice of media ownership is still being carried out and the massive government efforts to interfere with press affairs such as reviving the buzzer industry and acts of violence against journalists, press freedom has not really been felt even though the current conditions can be said to be better than before the reform era.